Scholastic Before and Scholarly After? Ukrainian Folklorists and Their Folklore after 1991 - Shostak, Natalia (Ethnologies, 1999)
After the collapse of the Soviet Union in 1991, Ukraine, like many other former Soviet republics, gained the new political status of an independent nation. Ukraine’s humanities and social sciences eagerly dissociated themselves from cultural legacies of the Soviet state and faced the need to promote their own projects of cultural revitalization, this time based on a national agenda. Folklore studies took an active part in this new national project of Ukraine. In this article, I am looking at one particular channel of the current folklore discourse in Ukraine, at the notion of folklore itself, analyzing its use, examining the ambiguity and multiplicity of meanings of its modifier “folk” [narodnyi]. I discuss how the notion of folklore is employed by Ukrainian folklore scholars in their attempts to redefine their discipline and to legitimize their newly emerged, supposedly homogenous Ukrainian nation. The verbalization, formulation, and conceptualization of the notion of folklore in today’s Ukrainian scholarship is an important discursive practice, making Ukrainian folklore an element of national property, and contributing to the nation-building processes.